General medicine : for UKMLA and medical exams - Eiben, Paola; Eiben, Inez; Hever, Pennylouise; Giles, Megan (Crash course, 2025)
Crash Course - your effective every-day study companion PLUS the perfect antidote for exam stress! Save time and be assured you have the essential information you need in one place to excel on your course and achieve exam success. Especially written by senior students or junior doctors - those who understand what is essential for exam success - with all information thoroughly checked and quality assured by expert Faculty Advisers, the result is books that exactly meet your needs and you know you can trust. Each chapter guides you succinctly through the full range of curriculum topics in the UKMLA syllabus, integrating clinical considerations with the relevant basic science and avoiding unnecessary or confusing detail. A range of text boxes help you get to the hints, tips and key points you need fast! A fully revised self-assessment section matching the latest exam formats is included to check your understanding and aid exam preparation. The accompanying enhanced, downloadable eBook completes this invaluable learning package.